Revealing The Impact Of The Teacher Mobilization Program On The Competency Of Elementary School Teachers In Bekasi City - Awiria, Awiria; Dalilah, Evi; Salsabila, Sabrina Putri (Jurnal Multidisiplin Sahombu, 2025)
He aim of this research is to determine the impact of the Teacher Mobilization program on teacher competency in Bekasi City Elementary Schools. This research was carried out in several elementary schools in Bekasi City, with the subjects being 2 elementary school clusters in Bekasi City, namely the Kranji Cluster and the Kota Baru Cluster. This research used descriptive qualitative research conducted over two months. The data collection process is through observations, questionnaires, interviews with Mobilization Teachers, and documentation results in the form of photos. The results of the research show that there is a significant impact of the Teacher Mobilization program on Teacher competency in Bekasi City Elementary Schools, this is proven by increasing the knowledge and skills of Teachers who have become Mobilizing Teachers, such as using digital learning media, actively participating in teacher competency improvement activities, starting trusted to be a resource for various activities, as well as fulfilling one of the qualifications to become a School Principal. The implications of this research indicate that the Teacher Mobilization program can have a good impact on teacher competency, especially in Bekasi City Elementary Schools, therefore it is hoped that similar programs will reappear so that the quality of education in Indonesia can improve.